Buddhist Ethics and Surrogate Problem in the Present Thai Society - Phramaha Ponchai Sirivaro; Phramaha Nantakorn Piyabhani; Phramaha Khwanchai Kittimedhi; Penphan Fuangfooloy (Soshum: Jurnal Sosial dan Humaniora, 2019)
Surrogacy is still a controversial topic in Thai society. Surrogacy issue has come to the public attention through a recent case where a couple that, for some reason, cannot get their baby from the surrogate mother and then decides to find a solution by bringing their case to the court. Though viewed medically, from assisted reproductive technology, surrogacy is an achievement on its own since it can provide good hands to those couples in need; it is still enshrouded by ethical, legal and medical issue. Ethically, it is still debatable whether being a surrogate mother is morally permissible. Then, who are the rightful parents of child born from surrogacy according to the law is still unclear. This vagueness in terms of law, may create a loophole where the surrogate mother can be accused of selling a child. This article attempts to analyze and propose a Buddhist guideline to solve the problems of surrogacy in the present Thai society.